The Effect of Catching Drills Using Softballs on the Reflexes of Futsal Goalkeepers at the Curup United Academy - Rizky Mulya Ramadhan; Mariska Febrianti; Megi Personi (Educative Sportive, 2026)
Reaction speed is a crucial physical component for futsal goalkeepers due to the fast-paced nature of the game and the limited playing area. Goalkeepers are required to respond quickly to unpredictable ball movements, including deflections and sudden shots. This study aimed to examine the effect of catching training using a kasti ball on the reaction reflexes of futsal goalkeepers at Academy Curup United. The research employed a quantitative experimental method with a one-group pre-test and post-test design. The sample consisted of futsal goalkeepers from Academy Curup United who participated in a structured catching training program using a kasti ball conducted over 14 training sessions, three times per week. Data were collected through reflex performance tests administered before and after the training program. The data were analyzed using descriptive analysis, normality and homogeneity tests, and a paired sample t-test. The results showed a significant improvement in goalkeepers’ reaction reflexes after the training intervention, with a significance value of 0.000 (< 0.05) and a t value of 12.006, which was greater than the t table value of 1.943. These findings indicate that catching training using a kasti ball has a positive and significant effect on improving the reaction reflexes of futsal goalkeepers. Therefore, this training method is recommended as an effective exercise program for enhancing goalkeeper performance in futsal.